Anesthesia for Cesarean Section - Capogna, Giorgio; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book examines every aspect of anesthesia in patients undergoing cesarean section. Anesthetic and surgical techniques are clearly described, with detailed guidance on indications and contraindications and identification of potential complications. Practical information is provided on postoperative analgesia, postoperative course and nursing, the significance of cesarean section for breastfeeding, and the occurrence of long-term problems and chronic pain after cesarean section. Other topics to be addressed include the history and epidemiology of cesarean delivery, effects on the fetus and neonate, ethical issues, the humanization of childbirth, and maternal expectations and satisfaction. While many books are available on obstetric anesthesia, none is exclusively devoted to cesarean section although it is one of the most frequently performed surgeries. Anesthesia for Cesarean Section will be appreciated by all anesthesiologists and will be a useful source of information for obstetricians, gynecologists, midwives, nurses, medical students, and trainees.
History of cesarean section -- Epidemiology, indications, contraindications and surgical techniques -- Selection of anesthesia methods -- Spinal anesthesia (drugs - technique) -- Epidural and CSE anesthesia (drugs - technique) -- Assessing the anesthetic block -- General anestesia (drugs - technique) -- Effects on the fetus, neonate and breastfeeding -- Choice of anesthesia for emergency cesarean section -- Surgical complications -- Complications due to anesthesia (general and regional) -- Postoperative analgesia -- Long term problems and chronic pain -- Humanization of cesarean section -- Medicolegal aspects -- Maternal expectations and satisfaction.
Keywords: Medicine; Anesthesiology; Obstetrics; Medicine & Public Health; Anesthesiology; Obstetrics/Perinatology.